Apocalipse social audiovisual - Malhado, André (2022)
This article discusses the theoretical problem of defining an audiovisual Lusophone cyberpunk world through its sonic environment. The study explores a sample of nine audiovisual narrative media to defend that Lusophone art represents a social apocalypse linked to a trend in dystopian fiction and outlined through soundscapes and cyborgs constituted by continuous realms of geology-life, nature-culture, and voice-body. I ask: What are the acoustic ecologies of the apocalypse? How is the audiovisual representation of technoscientific spaces and bodies capable of creating a Lusophony? My analytic method is qualitative, and the interdisciplinary perspective crosses tools from musicology, sociology, and posthumanism. I conclude that there is a ventriloquial and ecocritical voice where humans and nonhumansrelate. The appearance of these posthuman geo-subjects, defined by hybrid conditions, question racialization processes through the timbres they adopt. Another aspect is that music, everyday sounds, and Lusophony markersexpress resistanceformsin technoscientific societies. In short, in technoscientific and posthuman realities there is aLusitanian cyberpunk polyphony connected tolanguage, speech, music, sound design, noise, and silence.